Response to oxidative stress of peripheral blood mononuclear cells from multiple sclerosis patients and healthy controls - Pistono, Cristiana (Cell Stress Chaperones, 2019)
The complex scenario of multiple sclerosis (MS) pathology involves several mechanisms, including oxidative stress response. The heat shock proteins (HSPs) are important for the protection of the cells; however, their role in MS is not clear. The present research is focused on the response of peripheral blood mononuclear cells (PBMCs) to oxidative stress and to the involvement of HSP70-2 (a protein coded by the HSPA1B gene, located in the MHC class III). To this aim, we challenged PBMCs from MS patients and healthy controls with hydrogen peroxide. Specifically, PBMCs mitochondrial activity, HSP70-2 protein expression and the production of intracellular reactive oxygen species were assessed. These parameters were also related to the HSP70-2 rs1061581 polymorphism, which is linked to the risk of developing MS. Moreover, mitochondrial activity and HSP70-2 protein levels were also related to disease severity. Overall, our results indicate that PBMCs, from both MS patients and healthy controls, may display a similar response towards an oxidative insult; within this context, HSP70-2 does not seem to be central in the protection of PBMCs. Nevertheless, the HSP70-2 rs1061581 polymorphism is related to ROS levels and appears to have a role in the different expression of HSP70-2 under oxidative stimulus.